Emergent Biosensing Technologies Based on Fluorescence Spectroscopy and Surface Plasmon Resonance - Alessandra Camarca; Antonio Varriale; Alessandro Capo; Angela Pennacchio; Alessia Calabrese; Cristina Giannattasio; Carlos Murillo Almuzara; Sabato D’Auria; Maria Staiano (Sensors, 2021)
The purpose of this work is to provide an exhaustive overview of the emerging biosensor technologies for the detection of analytes of interest for food, environment, security, and health. Over the years, biosensors have acquired increasing importance in a wide range of applications due to synergistic studies of various scientific disciplines, determining their great commercial potential and revealing how nanotechnology and biotechnology can be strictly connected. In the present scenario, biosensors have increased their detection limit and sensitivity unthinkable until a few years ago. The most widely used biosensors are optical-based devices such as surface plasmon resonance (SPR)-based biosensors and fluorescence-based biosensors. Here, we will review them by highlighting how the progress in their design and development could impact our daily life.